2021
DOI: 10.1177/2325967120970916
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Upper Limb Injuries and Hip Range of Motion in Elementary and Junior High School Baseball Players

Abstract: Background: Shoulder and elbow injuries are major problems in baseball players. Tightness of the upper extremities has been reported as a risk factor for shoulder and elbow injuries in elementary and junior high school baseball players. However, few studies have been conducted on the relationship between decreased hip range of motion (ROM) and shoulder and elbow injuries. Purpose/Hypothesis: This study aimed to prospectively examine the relationship between hip ROM and throwing-related shoulder and elbow injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a cross-sectional study, these authors additionally reported that hip external rotation ROM on the back leg was significantly lower in injured high school baseball pitchers than in non-injured pitchers 17 . A previous prospective study showed that preseason decreases ROM in flexion bilaterally and internal rotation on the back leg were risk factors for shoulder and elbow injuries in elementary and junior high school baseball players 18 . Hip ROM has not been established as a risk factor for baseball-related injury.…”
Section: Discussionmentioning
confidence: 95%
“…In a cross-sectional study, these authors additionally reported that hip external rotation ROM on the back leg was significantly lower in injured high school baseball pitchers than in non-injured pitchers 17 . A previous prospective study showed that preseason decreases ROM in flexion bilaterally and internal rotation on the back leg were risk factors for shoulder and elbow injuries in elementary and junior high school baseball players 18 . Hip ROM has not been established as a risk factor for baseball-related injury.…”
Section: Discussionmentioning
confidence: 95%
“…Hip IR and ER. The IR and ER of the hip were measured in the prone position according to previous studies, 18,38 using the same goniometer used in SLRA measurement. One examiner stabilized the pelvis, while the other bent the knee on the measurement side at 90 and rotated the hip joint internally and externally until an end feel was detected with flexion at 0 .…”
Section: Physical Examinationmentioning
confidence: 99%
“…The SLRA, defined as the angle between the floor and the thigh, was measured with a digital goniometer (Digital Protractor with stainless blades; iGaging) used to measure the range of motion of joints in previous studies. 18,42 Heel-Buttock Distance. The HBD was measured to evaluate the flexibility of the quadriceps muscles.…”
Section: Physical Examinationmentioning
confidence: 99%